1989
DOI: 10.1007/bf02623638
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the human chondrocyte phenotype in vitro

Abstract: We report a culture scheme in which human epiphyseal chondrocytes lose their differentiated phenotype in monolayer and subsequently reexpress the phenotype in an agarose gel. The scheme is based on a method using rabbit chondrocytes. Culture in monolayer allowed small quantities of cells to be amplified and provided a starting point to study expression of the differentiated human chondrocyte phenotype. The cells cultured in monolayer produced type I procollagen, fibronectin, and small noncartilaginous proteogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
102
0
6

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(111 citation statements)
references
References 28 publications
3
102
0
6
Order By: Relevance
“…Dedifferentiation is a reversible process characterized by the cessation of type II collagen mRNA and protein synthesis and the induction of type I collagen mRNA and protein synthesis. When articular chondrocytes cultured in monolayer are subsequently transferred to suspension culture in semisolid media they "redifferentiate" and express the collagen and proteoglycan network consistent with hyaline cartilage over a period of weeks (Aulthouse et al, 1989;Benya and Shaeffer, 1982;Binette et al, 1998;Watt and Dudhia, 1988). Because the precise molecular mechanisms involved in the regulation of articular chondrocyte dedifferentiation and redifferentiation remain to be elucidated, we used a subtractive hybridization approach to study the early molecular events in the initiation of articular chondrocyte redifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Dedifferentiation is a reversible process characterized by the cessation of type II collagen mRNA and protein synthesis and the induction of type I collagen mRNA and protein synthesis. When articular chondrocytes cultured in monolayer are subsequently transferred to suspension culture in semisolid media they "redifferentiate" and express the collagen and proteoglycan network consistent with hyaline cartilage over a period of weeks (Aulthouse et al, 1989;Benya and Shaeffer, 1982;Binette et al, 1998;Watt and Dudhia, 1988). Because the precise molecular mechanisms involved in the regulation of articular chondrocyte dedifferentiation and redifferentiation remain to be elucidated, we used a subtractive hybridization approach to study the early molecular events in the initiation of articular chondrocyte redifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Agarose, a linear polysaccharide extracted from marine red algae, is a thermosetting hydrogel that undergoes gelation in response to a reduction in temperature. Chondrocytes cultured in agarose will maintain their phenotype and synthesize near normal levels of collagen II and proteoglycan (Benya and Shaffer 1982;Aydelotte and Kuettner 1988;Aulthouse et al 1989). Over time, chondrocyte seeded agarose hydrogels have been shown to produce a functional extracellular matrix in free swelling culture (Buschmann et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have examined the plasticity of the chondrocyte phenotype from many different species have consistently shown that culture of these cells in monolayers on plastic substrata for prolonged periods or upon repeated passages leads to the loss of their spherical shape and to the acquisition of an elongated fibroblast-like morphology (7,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). These morphologic alterations are accompanied by profound biochemical changes, including loss of the cartilage-specific phenotype, as evidenced by an arrest of the synthesis of the cartilage-specific collagens (types II, IX, and XI) and proteoglycans (aggrecan), initiation of synthesis of the interstitial collagens (types I, III, and V), and increase in the synthesis of fibroblasttype proteoglycans (versican) at the expense of aggrecan (7,17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%